Eliminación/Degradación de Triazinas Mediante Biorreactor de Membrana con Post-Tratamiento de Ozonización - Rodríguez, E.D. Vásquez; Llamas, M.J. Moya; Del Hombre Bueno, M.A. Bernal-Romero; Trapote, Arturo; Rico, Daniel Prats (KnE Engineering, 2018)
The aim of the research was to evaluate the removal of micropollutants in a combined system MBR + ozonation. The research was carried out in a MBR scale laboratory plant which was fed with synthetic wastewater, doped with simazine (SIM), atrazine (ATZ) and terbutilazine (TBZ). The MBR operational conditions were: hydraulic retention time (HRT) of 20 h, organic loading rate (OLR) of 0.23 KgCOD/KgSSV·day, sludge retention time (SRT) of 30 d, and flux of 5.5 LMH. Two ozone doses were tested: low dose (16 mg O3/L) and high dose (45 mg O3/L). The removal eficiency of organic matter was 96%. For the studied triazines, low biodegradation effiencies were reached by biological treatment (MBR): 57%, 53% and 63% for SIM, ATZ and TBZ, respectively. The complementary treatment of ozonation improved the quality of the effluents. At low ozonation dose the overall removal efficiencies increased to 95%, 92% and 96% for SIM, ATZ and TBZ, respectively. At high ozonization dose the overall removal efficiencies were 98%, 97% and 97 % for SIM, ATZ and TBZ, respectively, percentages slightly higher than those obtained at low dose. The results showed the combination of MBR + O3 is effective to remove micropollutants from wastewater, contributing to the preservation of a good ecological state of water bodies. Keywords: Bioreactor, Membrane, Ozone, Triazines, Herbicides.